A3.10 Serum calprotectinis elevated in patients with early rheumatoid arthritis but not in patients at risk of developing rheumatoid arthritis. (24th February 2016) - Prajzlerová, K; Cerezo, L Andrés; Hánová, P; Mann, H; Pavelka, K; Vencovský, J; Šenolt, L; Filková, M
Abstract : Background and objectives: Calprotectin (S100A8/S100A9 complex) is associated with disease activity, radiographic progression and may predict treatment response in patients with rheumatoid arthritis (RA). The aim of our study was to examine the serum levels of calprotectin in clinically suspect arthralgia patientswith positive antibodies to citrullinated peptide antigens (ACPA) who areat high risk of developing RA. Materials and methods: This cross-sectional study included 20 ACPA+ arthralgiapatients, 55 patients with early RA (disease duration <6 months who fulfilled 2010 ACR/EULAR classification criteria) and 68 healthy controls (HC). Disease activity was assessed using DAS28. Ultrasound of 28 small joints was performed in all patients with arthralgia to evaluate subclinical synovitis. Serum calprotectin levels were determined byELISA. Data were analysed using 1way ANOVA, Mann-Whitney test and Spearman's and Pearson's correlation coefficients. The data are expressed as mean±SD. Results: Patients with clinically suspect arthralgia showed no clinical and ultrasound evidence of arthritis (grey scale and power Doppler for single joint ≤ 1). Of these, all were ACPA+, 70%females; age 41.92 ± 11.72 years, CRP 7.39 ± 19.19 mg/l. Treatment naïve patients with early RA had active disease (meanDAS28:5.54 ± 1.62), 65% were ACPA+, 71% were females; age 54.17 ± 16.77 years and CRP 20.46 ± 26.66 mg/l. Serum calprotectin in clinically suspect ACPA+ arthralgia patientswas not significantly different compared to HC (2980 ± 1610 vs. 3368 ± 1624 ng/ml, p = 0.35) but was significantly lower in both groups compared to early RA (5977 ± 5787 ng/ml, p = 0.01 and 0.02 respectively). There was no correlation between calprotectin and CRP in suspect arthralgia patients, however, in early RA, serum calprotectin significantly correlated with DAS28 (r = 0.432, p = 0.001) and CRP (r = 0.670, p < 0.0001). Conclusions: Calprotectin is not increased in ACPA positive patients who have normal ultrasound findings of small joints and thus may not help to predict RA development in this early stage of the disease. However, calprotectin is significantly elevated in patients with active early RA, where it serves as a reliable biomarker of disease activity. Acknowledgements: IGA project no. NT 14498, project of MHCR 023728 and project SVV 260 155.